Kepuasan Muzakki Terhadap Kualitas Pelayanan Zakat Pada BAZ (Badan Amil Zakat) Kabupaten Kerinci - Hendrianto, Hendrianto (Sekolah Tinggi Agama Islam Negeri Curup, 2016)
The muzakki satisfication towards the service quality in BAZ (Badan Amil Zakat) is different each others. It is because of the complicated-factors. Based on that assumption, the research is focused to measure the muzzaki utility towards the service quality of BAZ, Kerinci District. Applied the quantitative method, the study result a main finding in which the trend of muzakki utility toward BAZ service is good enough. But, in other cases, a part of them feels not enough in satistification. It can be proved from the tangible (CM) score ON 211. Keywords: Muzakki utilty, Service, Quality, Satisfication and Zakat Apparatus.